2021
DOI: 10.3390/curroncol28030182
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pathological Complete Response and Resolution of Dermatomyositis Following Neoadjuvant Chemotherapy in HER2-Positive Early Breast Cancer

Abstract: Introduction. Dermatomyositis (DM) is an idiopathic inflammatory myopathy (IIM) mainly characterized by subacute muscle weakness and skin rash sometimes associated with malignancy. Case Presentation. A 61-year-old female was admitted to our hospital because of progressive proximal muscular weakness, heliotropic rash and left breast rash. Muscle biopsy findings were consistent with dermatomyositis (DM). A full panel of myositis associated (MAA) and specific antibodies (MSA) revealed the presence of anti-nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…26 After Dr. Piras et al gave both neoadjuvant and DM-related treatment, the patient's DM symptoms had largely recovered, mastectomy was performed, and the patient recovered well. 10 Controlling DMrelated symptoms before surgery reduces postoperative wound healing from DM, but the overall time to control the disease is longer than patients treated surgically first. Some clinicians believe it is critical to address tumor-related issues first, as DM may manifest as a paraneoplastic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 After Dr. Piras et al gave both neoadjuvant and DM-related treatment, the patient's DM symptoms had largely recovered, mastectomy was performed, and the patient recovered well. 10 Controlling DMrelated symptoms before surgery reduces postoperative wound healing from DM, but the overall time to control the disease is longer than patients treated surgically first. Some clinicians believe it is critical to address tumor-related issues first, as DM may manifest as a paraneoplastic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 According to epidemiological statistics, 15–30% of cases of DM are associated with malignancies. 10 A study from Asia showed that DM is the second most common disease associated with breast cancer in women. 11 There are no treatment guidelines related for breast cancer associated with DM, and individualized treatment is based on the clinical cases.…”
Section: Introductionmentioning
confidence: 99%